Risk Assessment and Risks of Assessment in the Work of Probation Officers - Ros, Jenny; Kloetzer, Laure; Lambelet, Daniel (Swiss Journal of Sociocultural Anthropology, 2020)
Our paper reports on research on risk evaluation and management conducted with three probation services in French- or Italian-speaking cantons in Switzerland. It analyzes how probation officers construct an understanding and evaluation of levels of risk of reoffending for people convicted and serving parts of their sentences in an open environment. Our analysis combines observations of and interviews with probation officers using a method called “instructions to the double”, as well as analysis of written records (personal files, evaluation grids). We show that the risk evaluation activity of the probation officers, which we view as a cognitive and social process, draws on different sources. It is characterized by the multiplicity and heterogeneity of the resources mobilized, its dynamic character over the course of the interaction, and its orientation towards risk management. In addition, its validity is also tested in formal or informal collective evaluations. We show, in conclusion, that it does not correspond to the standardized approach advocated in the criminological literature.